Performance analysis of space shift keying for AF relaying with relay selection - Öztoprak, Özgür Can; Yarkin, Ferhat; Altunbas, Ibrahim; Basar, Ertugrul (Elsevier BV, 2017)
Abstract In this paper, we propose an amplify-and-forward multiple-input multiple-output (MIMO) relaying scheme, which combines space shift keying (SSK) with the best and partial relay selection. In this scheme, SSK transmission is considered by using the source (S) transmit antennas. Besides the direct link transmission, a relay, which is selected according to the best or partial relay selection techniques, amplifies the data received from S and forwards it to the destination (D). Theoretical error probability expressions of the proposed cooperative SSK systems are derived and an asymptotic diversity analysis is also performed to demonstrate the achievable diversity orders of the systems. It is shown that the proposed SSK systems outperform the conventional cooperative single-input multiple-output (SIMO) systems. It is also revealed that there is an interesting trade-off between SSK with the best and the partial relay selection in terms of error performance and complexity as in conventional cooperative SIMO systems. However, it is shown that the partial relay selection provides an almost identical error performance compared to the best relay selection with a considerably lower complexity when the number of relays is less than or equal to the number of receive antennas at D in the cooperative SSK system.